Soil water harvest inspired by desert horned lizards, Phrynosoma platyrhinos - Seungjoo Lee; Junhee Choi; Wonseok Kim; Sohyun Jung; Sung Jae Kim; Wonjung Kim; Ho-Young Kim (Proceedings of the National Academy of Sciences, 2026)
Desert environments pose severe water scarcity challenges, leading to unique adaptations among native fauna. Notably, many species of desert horned lizards utilize a dermal drinking method, employing integumental microchannels to draw water from raindrops and moist soils via capillary action. However, the exact mechanism by which they eventually move the water collected between their jaws into their mouths remains elusive. Our research investigates this critical step in the drinking of desert horned lizards, Phrynosoma platyrhinos , revealing that the lizards use characteristic rhythmic jaw movements to achieve effective water intake. Inspired by their distinct water harvesting techniques, we have engineered an artificial soil water harvesting system that mimics these natural capillary flows and jaw movements to achieve water collection from soil. This system incorporates porous media to simulate water transport from soil and employs parallel plates to emulate lizard jaw actions, successfully demonstrating effective water collection and purification through integrated ion-exchange materials. This multifunctional system not only addresses the urgent need for water in arid regions but also simultaneously ensures the collected water’s purity, removing harmful contaminants like heavy metals.